ANALYSIS IMPLEMENTATION OF BACK REFERRAL PROGRAM DIABETES MELLITUS AND HYPERTENSION IN HOSPITAL X, JAKARTA - Riza Ambari; Mieke Savitri (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Since morbidity rate of Diabetes Mellitus and Hypertension in Indonesia increased, the number of referral in hospital automatically high. National Health Insurance and hospital burden also increase if the Back- Referral Program (BRP) has not been implemented yet. The impact of the ineffectiveness of Back-Referral Program also felt by Hospital "X" in Jakarta. This study aimsto analyze the effectiveness implementation of Back-Referral Program (BRP) Diabetes Mellitus and Hypertension in Hospital "X". Methods: This research was conducted in Hospital "X" of East Jakarta by using Qualitative Method. The informant are considered influential with Back-Referral Program (BRP) in Hospital "X" , consisting of Head of Medical Service Section, Internist Doctors, Nurses in internist station, Diabetes mellitus and Hypertension patients in Hospital “X”, Doctor’s in first health facility (FKTP) , BPJS pharmacy partner and Head of Health Services Primary Management Unit (MPKP) BPJS East Jakarta. Results: This study found an indication of medicine shortage in first health facility (FKTP). Lack of communication and coordination between BPJS, Hospitals, FKTP and BPJS pharmacy partner, and also less of monitoring and evaluation of Back-Referral Program (BRP) in hospital. Conclusions: Since Back-Referral Program (BRP) has not been implemented yet in Hospital “X” will induce long queue in internist station and caused the internist cannot examine and verify patients with properly.